Occupational Well-Being of International Business Travelers: The Role of Leader-Member exchange and Travel Days - Heikkilä, Milla (My University, 2016)
International business has increased enormously during the past years due to advanced communication technology, falling trade barriers and highly developed transportation. This transformation in business has created a new and ever increasing group of employees called international business travellers (IBTs). It is presumed that the nature and demand for an employee’s work is influenced by this increase in their respective mobility, having therefore an effect also on an individual’s experienced occupational well-being. This master’s thesis focuses on examining the effect of leader-member exchange (LMX), which refers to the quality of the relationship between the leader and the follower, on IBTs’ work engagement (vigor as a core component). Also, the effect of traveling days on IBTs’ burnout (job exhaustion as a core component) is studied. The theoretical framework is based on job demands-resources (JD-R) model and thus, both health impairment and motivational processes are studied. Data used in this study was collected from a larger research process conducted by the University of Vaasa. Therefore, this thesis focuses on reanalysing a part of that data, which was collected for a study examining IBTs’ psychological well-being. The data (N=436) was originally gathered with a web-based questionnaire and all the participants are employed by a Finnish software and services company. The results gained through correlation analysis and regression coefficient showed that high quality LMX, viewed as job resource, predicted vigor and decreased exhaustion among IBTs. In addition, it was noted that travel days, seen as job demand, predicted exhaustion, but had no influence on vigor. The findings indicate that organizations should pay greater attention to the complex nature of mobile work and to the pressure under which IBTs operate. Moreover, organizations should help supervisors and IBTs to establish high quality LMX relationships, and over time, both employers and employees will benefit.
Keywords: occupational well-being; leader-member exchange; international business traveller; work engagement; burnout; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|